2013
DOI: 10.1007/s00125-013-2957-2
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor agonist treatment reduces beta cell mass in normoglycaemic mice

Abstract: Aims/hypothesis Incretin-based therapies improve glycaemic control in patients with type 2 diabetes. In animal models of diabetes, glucagon-like peptide-1 receptor agonists (GLP-1RAs) increase beta cell mass. GLP-1RAs are also evaluated in nondiabetic individuals with obesity and cardiovascular disease. However, their effect on beta cell mass in normoglycaemic conditions is not clear. Here, we investigate the effects of the GLP-1RA liraglutide on beta cell mass and function in normoglycaemic mice. Methods C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
42
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 37 publications
(42 reference statements)
11
42
0
Order By: Relevance
“…The reduction in the beta cell mass in the RIPCreEr-EYFP mice probably reflects the elimination of almost all the INϩ cells expressing the transgene. It has been reported that normoglycemic CD-1 mice treated with liraglutide, a GLP-1r agonist, for 6 weeks had a decreased beta cell mass and in proliferation (14). In view of our present findings with bigenic mice, the observations in normoglycemic CD-1 mice suggest that the stimuli to secrete more insulin eliminated suboptimal beta cells, and that normal glucose levels was maintained by the cells still left in the islets.…”
Section: Discussionsupporting
confidence: 67%
“…The reduction in the beta cell mass in the RIPCreEr-EYFP mice probably reflects the elimination of almost all the INϩ cells expressing the transgene. It has been reported that normoglycemic CD-1 mice treated with liraglutide, a GLP-1r agonist, for 6 weeks had a decreased beta cell mass and in proliferation (14). In view of our present findings with bigenic mice, the observations in normoglycemic CD-1 mice suggest that the stimuli to secrete more insulin eliminated suboptimal beta cells, and that normal glucose levels was maintained by the cells still left in the islets.…”
Section: Discussionsupporting
confidence: 67%
“…␤-Cell cluster size was determined as the median size of ␤-cell clusters (defined as Ն4 ␤-cells per cluster) per mice. ␣-Cell mass was determined as previously described (14) by calculating the ratio of ␣-cell area to ␤-cell area, using Image J software (Image J; National Institutes of Health, Bethesda, MD) multiplied by the ␤-cell mass.…”
Section: Animalsmentioning
confidence: 99%
“…Changes in glucose metabolism are associated with adaptation of the number and/or function of ␤-cells to produce and secrete an adequate amount of insulin (6,34). Also ␣-cell mass can be modulated by dietary changes (14). Inadequate adaptation leads to glucose intolerance and eventually results in diabetes mellitus (9,21).…”
mentioning
confidence: 99%
“…Adult pancreatic islet cells are mostly in the quiescent/G 1/0 state but can re-enter cell cycle following appropriate stimuli. For example, the glucagon-like peptide-1 (GLP-1) analogue, exendin-4, stimulates beta cell proliferation [11,12] while preventing alpha cell expansion [13,14]. However, the mechanisms by which GLP-1 mediates these divergent effects in alpha and beta cells are unknown.…”
Section: Introductionmentioning
confidence: 99%